There is a relationship between knee and hip kinematics and the reduction of vertical ground reaction forces in youth soccer athletes - Stephenson, L. J.; DiStefano, L. J.; Padua, D. A. (Journal of Athletic Training, 2013)
It has been shown in adult populations that vertical ground reaction forces (VGRF) are absorbed primarily through altering knee kinematics and secondarily through changes in ankle angles in females and hip angles in males. As youth athletes demonstrate different landing biomechanics than that of adults it is prudent to assess their energy absorption strategies so that anterior cruciate ligament (ACL) injury prevention programs can address these changes in lower extremity kinematics to decrease forces at the knee. Objective: To identify relationships between decreased VGRF and knee and hip kinematic variables during a jump-landing task and determine how VGRF is being absorbed in youth soccer athletes. Design: Crosssectional. Setting: Research laboratory. Participants: Twenty-nine healthy soccer athletes (females: n=12, age=10±1 years, height =141.68±4.51cm, mass= 33.28±4.40 kg; males: n=17, age=10±1 years, h e i g h t = 1 4 1 . 5 9 ± 6 . 0 6 c m , mass=32.59±3,73kg) volunteered to participate. Interventions: Two sets of three jump-landing trials were performed during a single testing session. Participants were provided with instructions regarding proper landing technique prior to each trial of the second set of landings. The task required participants to jump forward from a 30cm high box placed adistance of half their height away from a force plate, land with their dominant foot on the force plate, and immediately jump for maximal vertical height. An optical three-dimensional motion analysis system and a force plate measured lower extremity kinematics and kinetics. Main Outcome Measures: Dependent variables included sagittal and frontal plane knee and hip angles at initial contact and peak values over the stance phase and peak VGRF which was normalized to body weight. Bivariate correlations were analyzed assessing the relationship between VGRF and all kinematic variables and were additionally analyzed by sex (d".05). Results: Analysis of all participants revealed significant moderate positive correlations between VGRF and hip flexion at intial contact (HFIC) (r(27)=.404, p<.05) and between VGRF and peak hip flexion (HFP) (r(27)=.442, p<.05). When analyzed by sex no significant correlations were found between VGRF and the kinematic variables for males, and females demonstrated a moderately strong significant negative correlation between VGRF and peak knee flexion (r(10)=-0.578, p<.05). Correlations between VGRF and knee flexion at initial contact (r(10)=.-0.573, p=.051) and peak knee valgus (r(10)=.-0.206, p=.052) were approaching significance. Conclusion: In order to decrease VGRF youth soccer athletes alter hip flexion. This landing strategy is in contrast to their adult counterparts who favor changes in knee kinematics as a strategy in decreasing VGRF. The females in this study demonstrated landing in a more erect posture with increased hip extension followed by increases in peak knee flexion to absorb VGRF; this is concurrent with the literature on landing strategies in adult females. By understanding these force absorption strategies we can construct a more comprehensive ACL injury prevention program for these young athletes.